Acute liver failure due to previously unrecognised dilated cardiomyopathy in a 17-year-old boy with Duchenne muscular dystrophy - Janowski, Kamil; Ziółkowska, Lidia; Boruc, Agnieszka; Witulska, Katarzyna; Janowska, Maria; Stefanowicz, Marek; Jarmużek, Wioletta; Pawłowska, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2020)
We present a case of fatal liver failure secondary to previously unrecognised dilated cardiomyopathy in a 17-year-old boy with Duchenne muscular dystrophy (DMD). Acute liver failure in the clinical course of decompensated dilated cardiomyopathy in patients with DMD is rare and carries a high mortality rate. Severe congestive heart failure should always be considered as a possible cause of acute liver failure. In our article we summarise current recommendations including diagnostic and therapeutic standards regarding cardiac care in patients with DMD. Regular cardiac evaluation according to recommendations may detect the early stage of dilated cardiomyopathy and allow the implementation of preventive pharmacological treatment. Multispecialist management increases the survival and provides a better quality of life for children with DMD.